Tracing the origins of lung fibrosis - Buckley, CD; Midwood, KS (Springer Nature, 2024)
A lung-specific fibroblast that normally provides a niche for alveolar cells has been identified as the predominant source of emergent inflammatory and fibrotic fibroblast subsets. This finding has major implications for the treatment of lung diseases.